1999
DOI: 10.1111/j.1651-2227.1999.tb01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional effects and management of diarrhoea in infancy

Abstract: The interactions between diarrhoeal disease and nutritional status are complex and synergistic. These are serious issues globally because they affect hundreds of millions of young children and annually cause >3 million deaths in children aged under 5y. Despite intensive field‐based and laboratory studies over three decades, many questions remain unanswered about the causes, pathophysiology and best approaches to management and prevention of this “diarrhoea‐malnutrition” syndrome. Oral rehydration therapy (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…From (50) children on cow milk there are 1(2%) discharged after 2 days, 4(8%) discharged after 3 days, 5(10%) discharged after 4 days and the other discharged after 5 days. From (50) children on breast feed 3(6%) of them discharged after 2 days, 8(16%) discharged after 3 days, 4(8%) discharged after 4 days and the others discharged after 5 days, Table (3). The present study also revealed the effects of feeding type on the stool consistency.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation

Role of Lactose free milk in Acute Diarrhea

عطية الجبوري,
فرهود الجبوري,
راشد السعدون
2023
Tikrit J. Pharm. Sci.
“…From (50) children on cow milk there are 1(2%) discharged after 2 days, 4(8%) discharged after 3 days, 5(10%) discharged after 4 days and the other discharged after 5 days. From (50) children on breast feed 3(6%) of them discharged after 2 days, 8(16%) discharged after 3 days, 4(8%) discharged after 4 days and the others discharged after 5 days, Table (3). The present study also revealed the effects of feeding type on the stool consistency.…”
Section: Resultssupporting
confidence: 64%
“…The impact of diarrheal diseases is more severe in the earliest periods of life, taking into account both the number of episodes per year and the hospital admission rates (2) . These are serious issues globally because they affect hundreds of millions of young children and annually cause more than three million deaths in children (3) . Any attempt to assess the severity of diarrhea in children should include attention to its acute and long-term effects (4) .…”
Section: Introductionmentioning
confidence: 99%

Role of Lactose free milk in Acute Diarrhea

عطية الجبوري,
فرهود الجبوري,
راشد السعدون
2023
Tikrit J. Pharm. Sci.
“…Vitaminas y micronutrientes: se considera el uso de Vitamina A (43) y del zinc (44)(45)(46)(47)(48)(49) .…”
Section: Alteración En La Fase Postmucosaunclassified